Is the right to education a justiciable-right? - González Tugas, Juan Andrés (Derecho Público Iberoamericano, 2015)
The work analyzes and systematizes the case-law of the Chilean higher courts of Justice which protects the “right to education” based on six constitutional rights: 1) the right to life, 2) the right to equal treatment, 3) the right to a due process, 4) the right to have parents to choose their children’s education, 5) the right to property, and 6) the freedom to buy all kinds of goods.